33: A CENSUS TECHNIQUE FOR THE RIO GRANDE TURKEY* - Robert L. Cook (Wildlife Society Bulletin)
ABSTRACT Winter roosts of the Rio Grande turkey (Meleagris gallopavo intermedia) in the Edwards Plateau of Texas were located, and landowners were asked to estimate the number of turkeys utilizing each roost throughout the winter. Counts of turkeys on sample roosts were made to determine the accuracy of landowners' estimates. Counts indicated that landowners in the western portion of the Plateau overestimated the number of turkeys by 7 percent over a 2‐year period. Landowners in the eastern counties overestimated the number of turkeys by 203 percent. Roost sites in the western counties were stable and were found in specific locations, but those in the eastern counties were not. The stability of the roost site influenced the ability of landowners to estimate the number of turkeys. The interview was a satisfactory technique of censusing turkeys in the western counties, but it was unsatisfactory in the eastern counties, where roosts were unstable.